Marriage Between Religions Based on Human Rights Perspectives - Nerisma Eka Putri; Khaidir Ali Junid; Muhammad Azkia Fahmi (Darma Cendika Catholic University, 2024)
The controversy over religious marriages is still a matter of legitimate recognition by the state. The provisions of this regulation have not been explicitly regulated in the Act No. 16 of 2019 on the Amendment of the Regulation of the Law No. 1 of 1974. So researchers are interested to know the establishment of marriages of different religions based on the human rights perspective in the decision of the Supreme Court No. 1400K/Pdt/1986. This research is analytically descriptive, with an empirical jurisprudential approach and using the type of library research, to describe in depth about the topic of marriage from a different religious perspective through the understanding of concepts, understanding marriage rules, analyzing and concluding the results of research. So it is concluded that this problem does not have a point of legal clarity and creates a legal vacuum, so that this practice does not get a place in the eyes of the law. This practice of marriage is considered difficult to implement, so not a few people submit to the trust of their partners to carry out the marriage. According to the International DUHAM instrument, marriages of different religions are deemed to violate the right of every human being to enter into marriage. So the practice of marriage of different religions in the country of Indonesia is established on the basis of the decision of the Supreme Court No. 1400K/Pdt/1986. It's supposed to have got the attention of the government by issuing a new legal regulation